KEBUTUHAN DAN HARAPAN PELANGGAN DI LEMBAGA PENDIDIKAN ISLAM - Hanim Afifudin; Prim Masrokan Mutohar (Program Studi Manajemen Pendidikan Islam, 2022)
Abstract This journal aims to describe the needs and expectations of customers in Islamic educational institutions. This journal uses a literature analysis method that is used to find out the description, which involves actual and factual references. The focus of this journal is the definition of customer needs and expectations in Islamic educational institutions, efforts to realize customer satisfaction in Islamic educational institutions, and follow-up on satisfaction in Islamic educational institutions. It is hoped that by understanding this journal, readers will be able to understand the management of customer needs and expectations in Islamic educational institutions and apply them in various educational activities.